Kolekcja muzykaliów z księgozbioru rodziny Maltzanów z Milicza w zbiorach Biblioteki Uniwersyteckiej w Poznaniu - Wronkowska, Sonia (Biblioteka Uniwersytecka w Poznaniu, 2014)
Celem artykułu jest prezentacja nieznanej dotychczas kolekcji muzykaliów pochodzącej z biblioteki rodziny Maltzanów z Milicza (Militsch) na Śląsku. Księgozbiór pałacowy w 1945 roku został zabezpieczony i przewieziony do Biblioteki Uniwersyteckiej w Poznaniu, gdzie przechowywany jest do dziś. Należąca do niego kolekcja źródeł muzycznych dokumentuje patronat muzyczny członków rodziny Maltzanów, szczególnie czasy panowania hr. Joachima Carla Maltzana (1786–1817) oraz hr. Joachima Alexandra Kasimira Maltzana (1817–1850). W księgozbiorze Maltzanów zachowały się muzykalia pochodzące z XVIII i XIX wieku: dwa duże zbiory utworów, 11 pojedynczych rękopisów oraz dwa druki zawierające łącznie 110 utworów. Analiza źródłowa i repertuarowa pozwala na wskazanie cech wyróżniających muzykę na dworze Maltzanów. Było to charakterystyczne instrumentarium: solowo wykorzystywana viola da gamba, waltornia i viola d’amore.

The article aims at presenting the unknown collection of musical documents from the book collection that formerly belonged to the Maltzan family of Milicz (German: Militsch) in Silesia. In 1945, the palace book collection was seized by the new Polish authorities and then transported to the Library of the Adam Mickiewicz University in Poznań, where it still remains in the library’s hoildings. The collection of music documents, sources and memorabilia, part of the larger Maltzan book collection, documents the musical patronage of the members of the family, in particular that of the times of Count Joachim Carl Maltzan (1786–1817) and Count Joachim Alexander Kasimir Maltzan (1817–1850). The Maltzan book collection includes music documents from the 18th and the 19th centuries: two large collections of scores, eleven single manuscripts and two prints containing collectively a hundred and ten works. A source and repertory analysis of the documents allow us to indicate distinctive features of the music played at the Maltzans court. They involved their choice of a particular selection of instruments: the viola da gamba as a solo recital instrument, the French horn and the viola d’amore.
The collection of musical documents from the book collection of the Maltzan family from Milicz at Poznań University Library
Keywords: muzykalia; music documents; Maltzanowie; the Maltzan family; Milicz; Śląsk; Silesia; Biblioteka Uniwersytecka w Poznaniu; Poznań University Library